Burden and predictors of M-pox suspected cases in a rural setting of Cameroon: implications for developing countries - Flaure Rasana P Nganmegni; Julienne Louise L Ngo; René G Essomba; Philippe S Nguwoh; Franck S Metomb; Emilienne Epee; Nadia Mandeng; Georges-Alain E Mballa; Yap Boum II; Marie Claire A Okomo; Christian N Taheu; Joseph Fokam (Journal of Infection in Developing Countries)
Introduction: M-pox is a re-emerging pathogen that is spreading rapidly in developing countries, presenting a serious health risk. Data are scarce on M-pox and its determinants in endemic countries such as Cameroon. This study aimed to assess the epidemiological burden and factors linked to the resurgence of M-pox in high-risk communities in Cameroon.